Experimental study on fatigue failure and damage of sandwich structure with PMI foam core. Issue 4 (22nd September 2014) - Yang, F.P.; Lin, Q.Y.; Jiang, J.J.
Abstract Sandwich structures consisting of aluminium skin sheets and polymethacrylimide foam core have been gradually used in the high‐speed trains. The static mechanical properties and fatigue damage of the sandwich structures with polymethacrylimide foam core were experimented in three‐point bending and were discussed. The failure mode is identified as local indentation. The static strength was obtained, and it showed good consistency with the forecasting formula. The fatigue property and damage evolution were also researched under cyclic loading. The fatigue life curve and the fitting formula were submitted. The fatigue damage evolution started from the skin sheet fracture and then the foam core indentation. The displacement at the midpoint as the damage parameter was discussed, and the evolution prediction formula was submitted, which showed great agreement with the experimental results.